2022
DOI: 10.3390/biomedicines10123189
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Alpha Oscillations among the Main Neuropsychiatric Disorders in the Adult and Developing Human Brain: Evidence from the Last 10 Years of Research

Abstract: Alpha oscillations (7–13 Hz) are the dominant rhythm in both the resting and active brain. Accordingly, translational research has provided evidence for the involvement of aberrant alpha activity in the onset of symptomatological features underlying syndromes such as autism, schizophrenia, major depression, and Attention Deficit and Hyperactivity Disorder (ADHD). However, findings on the matter are difficult to reconcile due to the variety of paradigms, analyses, and clinical phenotypes at play, not to mention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 252 publications
1
37
0
Order By: Relevance
“…This leads to the downregulation of fear reactions when the test context closely resembles the extinction context (Greco and Liberzon, 2016;Maren and Holmes, 2016;Craske et al, 2018). LeDoux (2022) suggests that the higherorder network involved in emotion regulation includes the lateral prefrontal cortex (PFC), encompassing the dorsal and ventral prefrontal cortex and the lateral frontal pole. The dorsolateral prefrontal cortex (DLPFC) is involved in the executive control of emotional expression and is more characteristic of higher-order emotion regulation processes (Schiller and Delgado, 2010;Battaglia et al, 2020).…”
Section: Reasons For Differences In the Efficacy Of Cognitive Reappra...mentioning
confidence: 99%
“…This leads to the downregulation of fear reactions when the test context closely resembles the extinction context (Greco and Liberzon, 2016;Maren and Holmes, 2016;Craske et al, 2018). LeDoux (2022) suggests that the higherorder network involved in emotion regulation includes the lateral prefrontal cortex (PFC), encompassing the dorsal and ventral prefrontal cortex and the lateral frontal pole. The dorsolateral prefrontal cortex (DLPFC) is involved in the executive control of emotional expression and is more characteristic of higher-order emotion regulation processes (Schiller and Delgado, 2010;Battaglia et al, 2020).…”
Section: Reasons For Differences In the Efficacy Of Cognitive Reappra...mentioning
confidence: 99%
“…The electroencephalogram (EEG) can be an accurate proxy of long-term clinical outcomes for patients with neuropsychiatric disorder that reflects damage to the neural network [ 12 ]. Patients with major depression disorder present rhythmic aberrations in prefrontal cortex recorded by EEG, which may be associated with changes occurring in cortical and subcortical loops related to cognition impairment, showing decrease in alpha connectivity especially [ 13 ]. This not only relates to depression symptoms of attentional impairment, suicidal ideation, rumination, and depression behavioral scale scores, depression severity and the curative effect of depression treatment, but has also been shown to significantly affect higher cognitive abilities [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with major depression disorder present rhythmic aberrations in prefrontal cortex recorded by EEG, which may be associated with changes occurring in cortical and subcortical loops related to cognition impairment, showing decrease in alpha connectivity especially [ 13 ]. This not only relates to depression symptoms of attentional impairment, suicidal ideation, rumination, and depression behavioral scale scores, depression severity and the curative effect of depression treatment, but has also been shown to significantly affect higher cognitive abilities [ 13 ]. Brain imaging has also revealed abnormalities in regional brain functioning associated with depression.…”
Section: Introductionmentioning
confidence: 99%
“…The prefrontal cortex has been shown to play an important role in social-emotional processing [ 10 ]. Frontal alpha asymmetry showed that major depression disorder (MDD) patients appeared to have increased alpha power in the left frontal hemisphere and decreased alpha power in the right hemisphere compared with control subjects [ 11 ]. When a person becomes depressed, he or she leaves the typical waking state and enters a separate global level of consciousness, such as dreaming or having psychedelic experiences [ 12 ].…”
Section: Introductionmentioning
confidence: 99%